Analisis Sifat Mekanis Magnesium Melalui Uji Tarik - Uum Sumirat; Asari Djohar; Iwa Kuntadi; Sigit Supriatno (Fakultas Teknik, Universitas Muhammadiyah Prof. Dr. Hamka, Jakarta, 2017)
Bone implant plates are only used temporarily during the healing process of a fractured bone. Once the healing process is complete, the implants need to be surgically removed. By using biodegradable material there will be no need for an implant removal surgery, because the implant plate will be degraded and destroyed naturally in the body. This biodegradable implant would need to bestrong enough to handle the body's weight and movement to be able to replace the bone physiologic function until the fractured bone is completely healed. A possible biodegradable material that could be degraded and destroyed naturally in the body is magnesium. However, magnesium has its limitation, its ability to resist corrosive properties is faster than a fractured bone healing process. Therefore, the plastic deformation process is done by suppressing the platewith 1%, 2%, and 3% degradation. It will increase the magnesium's ability to resist the dynamic force and improve its mechanical properties, so that the biodegradable implant plate can perform its function as a substitute for the fractured bone until the healing process is completed and degraded naturally only afterwards. The corrosive body fluid environment and recurring loads retained by the implant plate during the bone fixation process leads to fatigue of the implant plate.The crack rate testing of deformed magnesium alloys after immersion process in the physiological fluid DMEM can provide useful information on magnesium mechanical strength enhancement and subsequently whether it is feasible to be used as biodegradable bone implant plate.